Deception in plants: mimicry or perceptual exploitation? - Schaefer, H. Martin; Ruxton, Graeme D. (Trends in ecology & evolution (Amsterdam), 2009)
Mimicry involves adaptive resemblance between a mimic and a model. However, despite much recent research, it remains contentious in plants. Here, we review recent progress on studying deception by flowers, distinguishing between plants relying on mimicry to achieve pollination and those relying on the exploitation of the perceptual biases of animals. We disclose fundamental differences between both mechanisms and explain why the evolution of exploitation is less constrained than that of mimicry. Exploitation of perceptual biases might thus be a precursor for the gradual evolution of mimicry. Increasing knowledge on the sensory and cognitive filters in animals, and on the selective pressures that maintain them, should aid researchers in tracing the evolutionary dynamics of deception in plants.